A bioresorbable everolimus-eluting scaffold versus a metallic everolimus-eluting stent for ischaemic heart disease caused by de-novo native coronary artery lesions (ABSORB II): an interim 1-year analysis of clinical and procedural secondary outcomes from a randomised controlled trial. Issue 9962 (3rd January 2015) - Serruys, Patrick W; Chevalier, Bernard; Dudek, Dariusz; Cequier, Angel; Carrié, Didier; Iniguez, Andres; Dominici, Marcello; van der Schaaf, René J; Haude, Michael; Wasungu, Luc; Veldhof, Susan; Peng, Lei; et al.
Summary: Background: Despite rapid dissemination of an everolimus-eluting bioresorbable scaffold for treatment for coronary artery disease, no data from comparisons with its metallic stent counterpart are available. In a randomised controlled trial we aimed to compare an everolimus-eluting bioresorbable scaffold with an everolimus-eluting metallic stent. Here we report secondary clinical and procedural outcomes after 1 year of follow-up. Methods: In a single-blind, multicentre, randomised trial, we enrolled eligible patients aged 18–85 years with evidence of myocardial ischaemia and one or two de-novo native lesions in different epicardial vessels. We randomly assigned patients in a 2:1 ratio to receive treatment with an everolimus-eluting bioresorbable scaffold (Absorb, Abbott Vascular, Santa Clara, CA, USA) or treatment with an everolimus-eluting metallic stent (Xience, Abbott Vascular, Santa Clara, CA, USA). Randomisation was stratified by diabetes status and number of planned target lesions. The co-primary endpoints of this study are vasomotion (change in mean lumen diameter before and after nitrate administration at 3 years) and difference between minimum lumen diameter (after nitrate administration) after the index procedure and at 3 years. Secondary endpoints were procedural performance assessed by quantitative angiography and intravascular ultrasound; composite clinical endpoints based on death, myocardial infarction, and coronary revascularisation; device and procedural success; and angina status assessed by the Seattle Angina Questionnaire and exercise testing at 6 and 12 months. Cumulative angina rate based on adverse event reporting was analysed post hoc. This trial is registered at ClinicalTrials.gov, number NCT01425281 . Findings: Between Nov 28, 2011, and June 4, 2013, we enrolled 501 patients and randomly assigned them to the bioresorbable scaffold group (335 patients, 364 lesions) or the metallic stent group (166 patients, 182 lesions). Dilatation pressure and balloon diameter at the highest pressure during implantation or postdilatation were higher and larger in the metallic stent group, whereas the acute recoil post implantation was similar (0·19 mm for both, p=0·85). Acute lumen gain was lower for the bioresorbable scaffold by quantitative coronary angiography (1·15 mm vs 1·46 mm, p<0·0001) and quantitative intravascular ultrasound (2·85 mm 2 vs 3·60 mm 2, p<0·0001), resulting in a smaller lumen diameter or area post procedure. At 1 year, however, cumulative rates of first new or worsening angina from adverse event reporting were lower (72 patients [22%] in the bioresorbable scaffold group vs 50 [30%] in the metallic stent group, p=0·04), whereas performance during maximum exercise and angina status by SAQ were similar. The 1-year composite device orientated endpoint was similar between the bioresorbable scaffold and metallic stent groups (16 patients [5%] vs five patients [3%], p=0·35). Three patients in the bioresorbable scaffold group had definite or probable scaffold thromboses (one definite acute, one definite sub-acute, and one probable late), compared with no patients in the metallic stent group. There were 17 (5%) major cardiac adverse events in the bioresorbable scaffold group compared with five (3%) events in the metallic stent group, with the most common adverse events being myocardial infarction (15 cases [4%] vs two cases [1%], respectively) and clinically indicated target-lesion revascularisation (four cases [1%] vs three cases [2%], respectively). Interpretation: The everolimus-eluting bioresorbable scaffold showed similar 1-year composite secondary clinical outcomes to the everolimus-eluting metallic stent. Funding: Abbott Vascular.